ANALISIS KESALAHAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIK SISWA MTs - Mira Siti Hajar; Luvy Silviana Zanthy (Journal on Education, 2019)
This research aims to analyze the mistakes of students in solving mathematical problem solving capability as seen from the extent to which students make mistakes and find out the level of problem-solving ability matematiknya. In this study the methods used i.e. descriptive qualitative approach method. With the population in this research is the entire student MTs in Cimahi and samples in this study i.e. 20 grade VII in one of MTs in Cimahi. The results obtained from the study with the lowest percentage of mathematical problem solving capabilities with indicators identifying the elements of the adequacy of the data, and plan the steps to solve the problem of percentage low of 8% on question No. 2. and indicators make a mathematical model of a real situation in everyday life and doing the calculations to solve problems related to the system of linear equations of one variable of 9% on question No. 4. Less than students are able to create a mathematical model to good use. But in answering the question of students still have not been able to answer the question correctly. Students are only able to answer with mathematical modeling used in the linear equation of one variable. Students haven't been able to operate the linear equation of one variable. Thus, it can be concluded that the ability of problem solving is still classified as low visible from less usually students in making mathematical models and less usually students operate a linear equation in one variable solve tests mathematical problem solving ability.